Aplikasi Sistem Informasi Pencarian Tempat Kos Di Kota Bandung Berbasis Android - Dadi Rosadi; Feby Oktarista Andriawan (Jurnal Computech & Bisnis (e-Journal), 2016)
Now, to get the information place tenants in the greater bandung in detail and focused, especially through the android is still difficult obtained .Therefore, this research made to build an application mobile based android that can be facilitate the search and the owner tenants in search of and promote lodging house that is there Bandung City. Research methods used covering research methodology descriptive analytical and development, data collection method, and method of development a system based on object. The research results show that it takes an application search lodging to simplify search tenants to get informations lodging accurate so search tenants can be easily find a place lodging in accordance with the criteria desired. With a finish he made this application, will to simplify users in promoting and find a place tenants that is there bandung through the android.Keywords: information system; android.